Supply Chain Digitalization, Resilience, and Performance in the Apparel Sector of Sri Lanka - Kudamanna, Lihini (My University, 2025)
This study examines how digitalisation and resilience practices are adopted in the Sri Lankan apparel supply chain and how they affect the performance of the supply chain. The research seeks to comprehend the effects of digital tools, predictive systems, and organisational strategies to improvement in efficiency, visibility and risk management and countering technological adoption barriers. The three main goals were to determine the main digital and resilience practices rolled by the apparel manufacturers, determine their effect on the performance of the supply chain, investigate issues in the implementation, and make practical recommendations to firms and policymakers. The qualitative research approach was integrated and the collected data were semi-structured interviews and surveys conducted among key personnel of the chosen apparel manufacturers in Sri Lanka. The analysis of the data was an inductive thematic one, which allowed pointing out the common patterns, challenges, and performance outcomes. It was also based on the developed theoretical models, such as the Resource-Based View, the Technology-Organisation-Environment model, and the Contingency Theory to explain the results and place them in the context of the literature. The results show that companies that spent on ERP systems, automation, predictive analytics, and digital visibility have a higher accuracy rate, shorter cycle time, and disruption response. Multi-sourcing, scenario-based forecasting, and supplier monitoring are some of the resilience practices that enhance continuity of operations and preparedness to risks. The adoption is however limited by lack of skills, change resistance, cost, and lack of technical capability. Companies that systematise training, build a digital culture based on leadership, and imbue resilience as an ongoing work principle will deliver better results. The study has been both theoretically and practically relevant as it has shown the synergistic impact of digitalisation and resilience on the performance of a supply chain in an emerging economy setting. Industry implications are the focus on capabilities, systematic training on digital skills and team system ecosystems. To policy makers, industry wide transformation can be expedited by supporting the adoption of digital using financial incentives, training at sector levels, and standard frameworks. Comprehensively, the paper demonstrates the importance of the critical role of digital and resilience integration in improving global competitiveness and agility in the operation of the Sri Lankan apparel industry.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master’s Programme in Industrial Engineering and Management